2010
DOI: 10.3991/ijac.v3i4.1393
|View full text |Cite
|
Sign up to set email alerts
|

Impulse Purchasing Behaviors of the Turkish Consumers in Websites as a Dynamic Consumer Model: Technology Products Example

Abstract: This paper examines the concept of impulse purchasing behavior online basically. The phenomenon of impulse purchasing has been researched in consumer research as well as for example in psychology and economics since the 1950s. A detailed review and analysis of the literature asserts that there are some unsolved issues regarding the state of knowledge on impulse purchasing behavior. Furthermore, nowadays consumers buy an increasing amount of purchases on the Internet. The current conceptualizations of impulse p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…The use of colour can also in􀅫luence impulse buying behaviour. Research has shown that certain colours can evoke speci􀅫ic emotions and behaviours, and retailers often use this knowledge to create a sense of urgency or excitement in the user (Atici and Bati, 2010). For example, red is often associated with urgency and can be used to generate a sense of urgency to buy.…”
Section: Factors Affecting Online Impulse Buying Behaviourmentioning
confidence: 99%
“…The use of colour can also in􀅫luence impulse buying behaviour. Research has shown that certain colours can evoke speci􀅫ic emotions and behaviours, and retailers often use this knowledge to create a sense of urgency or excitement in the user (Atici and Bati, 2010). For example, red is often associated with urgency and can be used to generate a sense of urgency to buy.…”
Section: Factors Affecting Online Impulse Buying Behaviourmentioning
confidence: 99%
“…At the same time, IBB is the actual purchase that fulfils the strong desire preceding it [34]. Therefore, when individuals experience a sudden UBI, they may or may not act according to this strong feeling and purchase impulsively, which is the central aspect of IBB that distinguishes it from other types of buying behaviors, such as planned and unplanned buying [35][36][37][38][39][40]. Even though IBB and UBI are distinct concepts, most of the previous studies used UBI as a proxy to study the actual IBB [10,[21][22][23][24][25][26][27][28][29][30][31] as shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%